PENAKSIR UNTUK RASIO POPULASI DENGAN MENGGUNAKAN KOEFISIEN REGRESI DAN DUAL PADA VARIABEL TAMBAHAN - Nahriati Ersa; Sigit Sugiarto; Rustam Efendi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
In this article we discuss three estimators for population ratio using the coefficien regression and dual, which is a review from the article of Onyeka et.al [GlobalJournal of Science Frontier Research, 13(2013):57-65]. The three estimators are biased estimators and their mean square errorsare determined. Furthermore, this mean square errorsare compared to mean square error of each estimator.This comparison shows that thetype-product estimator is more efficient than another estimators.